Increasing water productivity and weed suppression of wet seeded rice: effect of water management and rice genotypes - Tuong, T.P.; Pablico, P.; Yamauchi, M.; CONFESOR, R.; Moody, K. (Cambridge University Press, 2000)
Weeds are major constraints to wider adoption of wet seeded rice. Two split-plot experiments on water management during crop establishment of wet seeded rice were conducted in the dry and wet seasons of 1994 to quantify crop stand establishment and weed suppression by herbicides and rice genotypes. The latter consisted of five previously identified hypoxic-tolerant lines and three standard cultivars, sown at approximately 300 seeds m−2. The tested hypoxic-tolerant genotypes had superior seedling growth, but not higher crop stand establishment than the standard ones. Genotypes that had superior crop stand establishment or faster seedling growth did not necessarily give better weed suppression. Genotypes with high tillering ability were more competitive against weeds. Echinochloa glabrescens dominated the weed flora, especially in farmers' practice and anaerobic seeding (seeding into soft mud), followed by flooding at 7 d after seeding (DAS). The relative proportion of Monochoria vaginalis increased in anaerobic seeding with flooding 3 DAS and seeding into standing water. Pretilachlor + fenclorim effectively controlled weeds in farmers' practice and anaerobic seedings, and 2,4-D in water seeding. Without herbicide, water seeding and anaerobic seeding flooded 3 DAS reduced dry weed weight by 73–88% compared with farmers' practice. Anaerobic seeding with flooding 7 DAS controlled weeds effectively when the weed pressure was low (dry season, about 136 g m−2 of weed biomass in plots without herbicide) but not when weed pressure was high (wet season, 513 g m−2). Water seeding could not sustain high rice yields due to low crop stand population caused by flotation of seedlings. Anaerobic seeding with flooding 3 DAS allowed genotypes to sustain high yield and increased water productivity (rice production per unit volume of water used in the field) without having to use herbicide or with only half of the recommended herbicide rate. The correct water management during the crop establishment stage may effectively lower the economic and possible runoff costs of herbicides without reduction in yield or water productivity.